Incidence and factors associated with reoperation after rotator cuff repair in Korea: A nationwide cohort study - Yee Ran Lyu; Eunkyoung Ahn; Doori Kim; Changsop Yang; Mi Hong Yim (PLoS ONE, 2026)
Introduction With the growing interest in rotator cuff repair (RCR), substantial evidence on factors associated with reoperation is crucial for decision-making. This retrospective longitudinal cohort study aimed to investigate the rate of rotator cuff reoperation after repair in Korea and identify factors associated with reoperation while considering the medical services implemented in Korea using the Korean National Health Insurance Database from 2011 to 2021. Methods Reoperation rates in patients who underwent RCR during a 3.5-year follow-up period were analyzed using Kaplan–Meier analysis. Pre-, intra-, and post-operative factors were analyzed using Cox proportional hazards regression model analyses. Results This study included 221,361 patients, among whom 15,089 (6.82%) underwent rotator cuff reoperation during the follow-up period, reflecting mid- to long-term reoperation (6 months to 3.5 years after surgery), rather than overall surgical failure. Sex, age, health insurance type, healthcare institution type, comorbidities, primary RCR type, arthroscopy use, primary diagnosis of primary RCR, and time to the first outpatient visit for Korean medicine healthcare or conventional medical healthcare were associated with rotator cuff reoperation. Conclusion Our results may help perioperative decision-making and postoperative management strategies related to reoperation risk, while considering patient characteristics, and may support counselling regarding the timing of postoperative care.